ANTIOXIDANT EFFECT OF MENTHONE ON INSULIN RESISTANT 3T3L-1 ADIPOCYTES CELLS (International Journal of Food and Nutritional Sciences, 2022)
Insulin resistance is caused by diminished glucose uptake in adipose tissue, an important insulin target tissue.Our current hypothesis was to delineate the effects of the menthone on antioxidant parameters and insulin signaling proteins in insulin resistant adipocyte cells. Our results found that TBARS level were significantly increased and the antioxidants such as SOD, GSH levels were diminished in insulin resistant cells. Furthermore, the expression of p-IRS1, PPAR-γ, p-Akt and p-PI3K were significantly decreased in the insulin-resistant adipocytic cells. Treatment with menthone significantly increased the expressions of above noted insulin signaling molecules and restored antioxidant status in insulin resistant cells. We conclude that menthone act as insulin sensitizer and could be used as dietary supplements in insulin resistance patients.